2010
DOI: 10.1111/j.1600-0528.2010.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Are oral health complaints related to smoking cessation intentions?

Abstract: We found no direct relation between oral health complaints and the intention to quit smoking, but oral health complaints and especially teeth discolouration were related to factors influencing the quit intention. Patients with discoloured teeth are more likely to have a positive attitude towards smoking cessation but are uncertain to persist smoking cessation. It is suggested that teeth discolouration can be a good entrance for addressing smoking cessation in daily dental practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…Further, dental patients may be more concerned with retention of their teeth and consequently more open to intervention on this topic due to the "8020 Movement", a program promoting retention of 20 teeth till 80 years of age which has been the national objective for oral health since 1989 in Japan. Tooth discoloration was presented to the third-most patients, and presenting this topic enhanced motivation the second-most intensively in the public, a finding which agreed with those of previous studies that suggested similar effects of presenting discoloration of teeth on promoting the intention to quit [25,26].…”
Section: Discussionsupporting
confidence: 87%
“…Further, dental patients may be more concerned with retention of their teeth and consequently more open to intervention on this topic due to the "8020 Movement", a program promoting retention of 20 teeth till 80 years of age which has been the national objective for oral health since 1989 in Japan. Tooth discoloration was presented to the third-most patients, and presenting this topic enhanced motivation the second-most intensively in the public, a finding which agreed with those of previous studies that suggested similar effects of presenting discoloration of teeth on promoting the intention to quit [25,26].…”
Section: Discussionsupporting
confidence: 87%
“…In 2010, Roseel et al ( 34 ) related the reasons for dental consultation and factors that might encourage a patient to consider quitting, with no correlation shown in general terms between the reason for the check-up and any intention to quit smoking. However, clinical findings such as discoloration of teeth might change the patient’s perception on the effect smoking has on oral health, besides periodontal problems.…”
Section: Discussionmentioning
confidence: 99%
“…A brief intervention using available resources on the various oral effects of smoking (eg, tooth discoloration), which can visually depict the effects, was effective in educating dental patients who were not ready to quit. 16 , 29 This approach is unique to the dental setting; dental clinics are therefore a health resource for organizing interventional programs for smokers, independently of medical facilities.…”
Section: Discussionmentioning
confidence: 99%